2015
DOI: 10.1061/(asce)up.1943-5444.0000239
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impacts of Bike-to-Work Day Events and Identifying Barriers to Increased Commuter Cycling

Abstract: Despite much enthusiasm among practitioners to spur rates of bicycle commuting via promotional measures such as community rides or commuter incentive programs, there is little research regarding their impact. Using data from one such event, Bike-to-Work Day (BTWD), this paper aims to understand the following: (1) who attends BTWD; (2) the impacts of these event-based promotional strategies across different groups; and (3) lessons for increasing commuter cycling in general. The authors assess these research que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Such events might last from a single day to months and might include rewards, giveaways, or competitions. Such promotions aim to raise awareness of cycling in the short term and increase cycling mode share to work in the long term ( Piatkowski et al, 2015 ; Rose and Marfurt, 2007 ). Other ways to advocate for cycling are the open street programs (Ciclovias) , in which streets are closed to motor vehicles and available to individuals for leisure activities ( Torres et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such events might last from a single day to months and might include rewards, giveaways, or competitions. Such promotions aim to raise awareness of cycling in the short term and increase cycling mode share to work in the long term ( Piatkowski et al, 2015 ; Rose and Marfurt, 2007 ). Other ways to advocate for cycling are the open street programs (Ciclovias) , in which streets are closed to motor vehicles and available to individuals for leisure activities ( Torres et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral intentions are formed by a rational assessment regarding attitudes toward a specific behavior (behavioral beliefs and outcome evaluations), subjective norms (beliefs about approval or disapproval from important others regarding the behavior), and perceived behavioral control (beliefs about factors that may facilitate or impede the behavior) (Ajzen, 1991). Many studies have found that sociopsychological variables derived from the TPB such as attitudes, social norms, and perceived behavioral control predict the likelihood to cycle (Dill, Mohr, & Ma, 2014;Fernandez-Heredia, Monzon, & Jara-Diaz, 2014;Heinen & Handy, 2012;Lois, Moriano, & Rondinella, 2015;Piatkowski et al 2015). In a review of psychological determinants of active travel, it was concluded that the TPB variables could predict active transport (Panter & Jones, 2010), but that there seemed to be a strong interaction with habit strength (Aarts, Verplanken, & vanKnippenberg, 1997), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Bike-to-work social media campaigns provide a valuable platform for tracking and sustaining behavior change, by creating a new database of participants for future targeted interventions, including hints and reminders (Mcmanus & Smith, 2005). This facilitating stage is to provide simple incentives to encourage early involvement in cycling programs, for example providing proper bicycle parking facilities and cycling paths on campus (Piatkowski et al, 2015).…”
Section: Campaign Educate Facilitatementioning
confidence: 99%